Enhancement of Cloud Security Using Enhance Multiplicative Inverse: Integrating MD5 and Multiplicative Inverse for Enhanced Cloud Security (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this research paper the discussion has been regarding cloud computing and services offered by it. This chapter focuses on the threats to cloud environment from external attacks. In order to make comparative analysis several existing researches have been discussed. The loop holes of those researches are considered. Then a proposed model with integration of MD5 and multiplicative inverse has been developed. This work has introduced more security to the cloud environment. More over the size of packet got reduced that result in high performance of system. The system is more secure and reliable due to integration of two cryptographic mechanisms.